DIABETES MELLITUS AND ARTERIAL HYPERTENSION (World Bulletin of Public Health, 2024)
Numerous studies have shown that diabetes mellitus and arterial hypertension are similarly associated with increased cardiovascular mortality. The presence of both diseases increases the risk of death by 2-fold. In 80% of cases diabetes mellitus is accompanied by arterial hypertension [1, 2]. The close relationship between these diseases is based on the unity of pathogenetic links, in particular, insulin resistance and hypersympathicotonia.
Keywords: arterial hypertension; type 2 diabetes mellitus; macro-microangiopathy